Stimulation of Growth and Development of Pandalungan Toddler in Indonesia - Lantin Sulistyorini; EkaAfdi Septiyono; NuningDwi Merina; PeniPerdani Juliningrum; Ira Rahmawati (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: The delay in growth and development is still a serious problem for both developed and developing countries in the world. One of the factors that cause delays in growth and development in toddlers is the lack of early stimulation of toddler development.Solving the problem of child growth and development cannot be separated from the existence of cultural diversity.Method: The qualitative research methods through a phenomenological approachwas chosen as the approach because this study tried to explore parents’ behavior in fulfilling the growth and development stimulation of the Pandalungan ethnic group.The sampling technique in this study used purposive samplingParticipants in this study were 15 participants with in-depth interviews used a semi-structured interview. Results: The results of the research get three main themes, and each theme has a sub-theme. The theme of stimulation from the family (Interaction with family, Parent’s Education, Parent’s Economic and Technology).The theme stimulation from social (Interaction with neighbors and government regulation). The theme Stimulation from culture and value(Cultural factors and values in society and Religious factors).Conclusion: The role of the family is needed in stimulating the growth and development of children because it will affect the growth and development of children.Social influences and government policies affect parents in stimulating growth and development. Culture and values will affect the growth and development of children because children are raised in that environment, so that they must follow the rules in the social environment.